Case Study of Schizophrenia – Qualitative Analysis - Samia Azeem; Dr. Anila Sadaf (Research Journal of Psychology, 2025)
This article presents a qualitative case study of a 28-year-old woman diagnosed with schizophrenia, capturing her symptoms, treatment, and the impact on her daily life. Using qualitative thematic analysis, we examine her subjective experience, the perspectives of her family, and the therapeutic approaches employed. This study aims to shed light on the challenges patients with schizophrenia face, the significance of family involvement, and the need for structured, multifaceted interventions. This case study demonstrates the multifaceted challenges that individuals with schizophrenia encounter. The qualitative analysis underscores the role of family, the need for a supportive environment, and the significance of an integrated therapeutic approach. Schizophrenia, with its complex symptomatology, requires both individualized treatment and systemic support for effective management and recovery.